Construction of a Model for Traditional Village Landscape Design System in Xuzhou City from a Low-Cost Perspective - Wang, Lian; Mayusoh, Chanoknart; Inkuer, Akapong; Puntien, Pisit (วารสารศิลปกรรมและการออกแบบแห่งเอเชีย, 2024)
This article examined the construction of a model for traditional village landscape design in Xuzhou City, Jiangsu Province, from a low-cost perspective. Addressing key problems in the protection and development of traditional village landscapes, the research employed sampling surveys, literature reviews, and data analysis to investigate the environment and landscape needs of villagers in 22 famous traditional villages in Xuzhou City, Jiangsu Province. The data was collected and analyzed by using ArcGIS, Spars, and other data analysis tools to explore the core elements and influencing factors of traditional village landscape design in the Xuzhou area. The study proposed principles and strategies for low-cost landscape design and explored a low-cost control model using the Marxist economic cost formula. Additionally, a systematic review of design principles from economic and sociological perspectives was conducted, leading to the development of a comprehensive low-cost design system model. This model provides both theoretical foundations and empirical guidance for the sustainable protection and development of traditional village landscapes in Xuzhou City.